Superconductivity of structurally disordered Y5Ir6Sn18. Issue 26 (20th June 2022) - Levytskyi, Volodymyr; Carrillo-Cabrera, Wilder; Akselrud, Lev; Kundys, Bohdan; Leithe-Jasper, Andreas; Gumeniuk, Roman
Abstract : The large Y5 Ir6 Sn18 crystal was grown from Sn-flux. Its structural and physical properties have been studied. Abstract : The structural and physical properties of Y5 Ir6 Sn18 grown from Sn-flux as large single crystals are studied. Y5 Ir6 Sn18 crystallizes with a unique structure [space group Fm 3̄ m, a = 13.7706(1) Å], which is characterized by a strong disorder. A transmission electron microscopy (TEM) study indicated that the structural model of Y5 Ir6 Sn18 obtained from X-ray diffraction methods is an average description of a complex intergrowth of domains with different structural arrangements. The studied stannide is a type-II superconductor with a critical temperature T c = 2.1 K, a rather weak electron–phonon coupling and conventional s-wave BCS-like mechanisms. Performed theoretical electronic band structure calculations indicated the inconsistency of an idealized structural model earlier reported for Y5 Ir6 Sn18 .